‘Planning over programs’: Challenges and opportunities affecting the participation of underserved producers in the conservation reserve program across the southeastern United States - Parag Kadam; Alejandro Bolques; Alex Harvey; Alton Perry; Sherwynn Best; Danielle Atkins; Felicia Burke; Lincoln Larson; Erica Rieder; Kayla Stukes; Sam Cook; Ben Graham; et al. (Conservation Science and Practice)
Abstract Black and female agricultural producers (farmland owners and operators) have traditionally been proportionally underrepresented and underserved in federal conservation programs. The Conservation Reserve Program (CRP), one of the largest conservation programs for private producers, had only 3.5% of participants from underserved populations in 2022. Increasing their participation is not only crucial for addressing historical inequalities but also essential in meeting nationwide conservation goals, especially when the participation of underserved stakeholder groups has been linked to more effective biodiversity restoration and land stewardship across numerous studies. This study employed mixed method analysis and demographic assessments to gain insights into the factors influencing the participation of underserved producers in CRP across six southeastern United States (US). Lack of knowledge about CRP emerged as the most significant challenge, followed by limited resources, lack of trust in the government, onerous program requirements, and other factors such as family or personal issues, or other priorities and motivations not centered on conservation. The study also identified several categories of solutions to increase the participation of underserved producers in CRP, including improving knowledge about the program, enhancing communication, increasing community involvement, and simplifying program requirements. Results indicate that, despite historical disparities in enrollment, Black producers may exhibit a higher likelihood of participation in CRP than White producers once they are aware of and engaged with the program; this is also likely for farm‐ and pastureland owners and potential operators who do not own land. Finally, the results of the two‐sample t‐test showed that the familiarity of females was lower than that of males. Our findings emphasize the importance of addressing historical knowledge gaps, overcoming resource challenges, building trust, simplifying program requirements, promoting empowerment through community involvement, and fostering conservation motivations to diversify program engagement. To that end, prioritizing proactive and needs‐based planning would help to ensure that CRP aligns with community needs and preferences. Strengthening the participation of Black and female producers in CRP simultaneously contributes to the twin goals of conserving environmentally sensitive lands and promoting program access.